Implementasi P5 Pada Sekolah IKM Kategori Mandiri Berubah - Dalia, Ade; Darlianti, Eneng; Haeriah, Yayah; Mardiana, Cucu (Jurnal Gentala Pendidikan Dasar, 2024)
This study aims to determine the description of the implementation of the Pancasila Student Profile Strengthening Project in the implementation of the Merdeka Curriculum in class IV UPTD SDN 2 Purwaharja Banjar City, which is included in the IKM implementing school in the Independent Change category. The method used is descriptive with a qualitative approach, while the data is collected using interview, observation, and documentation techniques as well as literacy studies. In the interview technique, the researcher determines the respondents to collect data, namely the principal, grade IV teacher, PJOK teacher, and PAI teacher. While in the observation technique, researchers obtained data from class teachers who filled out observation sheets. The data that has been collected is then analyzed and conclusions are drawn. The results of this study found that the Education Unit already knows how to plan the implementation of P5, the stages of implementing P5 and how to evaluate the implementation of P5 but not yet comprehensive and in-depth so that it affects the results that have not been maximized. In this study also found supporting and inhibiting factors for the implementation of the Pancasila Student Profile Strengthening Project at UPTD SDN 2 Purwaharja Kota Banjar, The supporting factors are the collaboration of all stakeholders, the school environment, and the supportive culture of the surrounding community. While the inhibiting factors are the diverse characteristics of students, teachers who do not understand and master the concepts and technical implementation, as well as the limitations of the implementation.